2009
DOI: 10.3174/ajnr.a1894
|View full text |Cite
|
Sign up to set email alerts
|

BLADE in Sagittal T2-Weighted MR Imaging of the Cervical Spine

Abstract: BACKGROUND AND PURPOSE:Image quality and diagnostic reliability of T2-weighted MR images of the cervical spine are often impaired by several kinds of artifacts, even in cooperative patients. The aim of this study was to evaluate if BLADE sequences might solve these problems in a routine patient collective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 24 publications
2
30
1
1
Order By: Relevance
“…In our routine patient collective consisting of mainly cooperative patients and a few patients with restricted ability to cooperate, motion artifacts were sufficiently corrected by the rotating kspace coverage in the BLADE technique with its repeated measurement of central k-space areas, although the dedicated motion correction algorithm was switched off in this study. This result is in good agreement with prior studies of the PROPELLER or BLADE technique in MRI of the brain [21 -23] and spine [19,20]. In the clinical routine motion artifacts often require repeated sequence acquisitions, thus prolonging the overall time of the examination and impairing patient comfort and departmental workflow.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our routine patient collective consisting of mainly cooperative patients and a few patients with restricted ability to cooperate, motion artifacts were sufficiently corrected by the rotating kspace coverage in the BLADE technique with its repeated measurement of central k-space areas, although the dedicated motion correction algorithm was switched off in this study. This result is in good agreement with prior studies of the PROPELLER or BLADE technique in MRI of the brain [21 -23] and spine [19,20]. In the clinical routine motion artifacts often require repeated sequence acquisitions, thus prolonging the overall time of the examination and impairing patient comfort and departmental workflow.…”
Section: Discussionsupporting
confidence: 90%
“…1, 2). Most of these factors have been evaluated separately in former studies [19,20], which showed improved spinal cord/CSF contrast in BLADE by reduced overall motion artifacts and improved image sharpness. The better and clearer the spinal cord is visualized, the easier spinal lesions can be identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T 2 -weighted imaging is a very common clinical imaging contrast; amongst other applications, it plays a crucial role in the detection of gray and white matter lesions such as in multiple sclerosis [1,2], Alzheimer's disease [3], and cancer [4]. This imaging technique should benefit from the increased signal-to-noise ratio (SNR) available at high field strengths (B 0 ≥ 3T), allowing acquisitions with higher spatial resolution and hence better visualization of small brain structures.…”
Section: Introductionmentioning
confidence: 99%